WANPRESTASI DALAM PERJANJIAN BANGUN BAGI RUKO (STUDI PUTUSAN NOMOR: 514/PDT.G/2013/PN-MDN) - WINDA IMOYATI MANIK (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. T. Keizerina Devi A3. Dedi Harianto The case in Ruling No. 514/Pdt.G/2013/PN-Mdn was started with a construction cost sharing agreement of a house and determination of its parts between the land owner Mrs. AA , and the developer Mr. BB on April 21, 2009, that they would construct 5 (five) units of shophouses on Mrs. AA’s land by the developer. It was agreed that Mrs. AA would get 2 (two) units and Mr. BB would get 3 (three) units, in which the construction of Mrs. AA’s units would have been completed no longer than 12 (twelve) months. However, the construction of Mrs. AA’s shophouses had not been completed until 2013. Mrs. AA filed a lawsuit against Mr. BB to annul the agreement and indemnify the financial injuries due to the default done by the developer. The objective of this study is to discover the cause of the default in the construction cost sharing agreement of the shophouses, the legal protection for the land owner due to the developer’s default, and the consequence of the default to the third party as the buyer of the object of this case.Keywords: Default, Agreement, Construction cost sharing